Climatology Influence on Malaria Cases in Alusi Community Health Center, West Southeast Maluku Regency - Sandy, Semuel; Ayomi, Ivon (KEMAS: Jurnal Kesehatan Masyarakat, 2018)
The west Southeast Maluku regency is a malaria endemic area with API of 29.99 / 1000 in 2014. Malaria is affected by climatology, therefore climatological changes can be used to predict increase in malaria cases. We used times series study research method of the climatology influence on malaria cases in Alusi Community Health Center. We used secondary data of malaria cases from Alusi Community Health Center and climatologic data (rainfall, wind speed, humidity temperature) from Saumlaki Meteorological, Climatology, and Geophysical Agency. The research was conducted in March-April 2016 in West Southeast Maluku Regency.Ã‚Â  The data was analysed by linear regression. The proportion of malaria cases was 38.3%; most infection occured in patients over 15 years old (71 cases). The linear regression analysis of climatological influence on malaria cases were as follows: humidity was r = 0.382; R2 = 0.146; p = 0.220, r = 0.172 temperature was; R2 = 0.03; p = 0.592, r = 0.345, rainfall was; R2 = 0.119; p = 0.272, and wind velocity was r = 0.07; R2 = 0.005; p = 0.828. We could concluded that climatology parameters showed positive correlation, but statistically insignificant relationship with malaria cases (p <0.05).